Strategi Pengembangan UMKM Bantal Kapuk untuk Peningkatan Daya Saing: Sebuah Analisis SWOT dan QSPM - Wanti Nawangsari; Resti Prastika Destiarni (JSEP (Journal of Social and Agricultural Economics), 2023)
Technological developments that affect lifestyles in society will also have an impact on existing MSMEs. The important thing that MSMEs must consider in maintaining their business in the midst of high competition is their marketing activities. One of the MSMEs that must survive is the Kapok Pillow MSME in East Lenteng Village. The purpose of this study is to identify internal and external factors that influence the marketing of kapok pillow businesses and to analyze marketing strategies for increasing the competitiveness and existence of kapok pillow businesses through a marketing mix approach. The method used is IFE, EFE, SWOT, and QSPM analysis. The results of the analysis show that these MSMEs are in quadrant 1, which means that MSMEs have opportunities and strengths that can be exploited. In addition, 9 alternative strategies can be implemented, obtained from a combination of internal and external factors from the company. The priority strategy suggested is to maintain product quality at competitive prices according to the raw materials used. It is hoped that the village government and related agencies can assist MSMEs in developing their business both in terms of production and marketing.